Keterampilan Kerjasama Siswa Dalam Pembelajaran Biologi Melalui Penerapan Cooperative Learning Tipe Student Team Achievment Divisions (STAD) dan Think Pair Share (TPS) - Roro Putri Nur Azmi Saputra Wijaya; Meti Indrowati; Yudi Rinanto (Universitas Sebelas Maret, 2019)
This study aims to determine differences in cooperative learning model STAD and TPS on cooperation inbiology learning skills class XI student of Mathematics. This research is a quasi-experimental design quantitative Posttest- Only Control Design. The study population was a class XI student of Mathematics and Science High School N 6 Surakarta in the academic year 2018/2019 amounted to 166 students consisting of 5 classes. The sampling technique using cluster random sampling study. This research conducted in two classes: Class XI Mathematics 2 were 36 students as classroom experiments A cooperative learning model STAD and XI MIPA 4 as class B experiments with cooperative learning model TPS. Data collection technique used method of observation to observation sheet cooperation skills Crebet and refer to the indicators. Data analysis using descriptive statistical analysis techniques. Prerequisite test hypotheses using normality test and homogeneity test. Hypothesis test used is the independent sample t-test with a significance level of 0.05. Assisted data analysis using SPSS 16. The results showed that the average value of the experimental class A collaboration skills with STAD cooperative learning model that is 84.09 higher than the average value of cooperation skills class B experiment with cooperative learning model TPS is 77.50. Based on the results of this study concluded that there are differences of class XI student collaboration skills of Mathematics and Science in biology learning through the implementation of cooperative learning model STAD and TPS.